2015
DOI: 10.5861/ijrset.2016.1428
|View full text |Cite
|
Sign up to set email alerts
|

Faculty attitude and use of ICT in instructional delivery in tertiary institutions in a developing nation

Abstract: This study is a survey aimed at ascertaining the attitude of academic staff in tertiary institutions in Imo State Nigeria towards the use of information and communications technology (ICT) in teaching. It also examines their level of use of ICT for teaching and learning purposes. The paper also compares the attitude of the faculty by gender and type of the institution they teach in, i.e. college of education, polytechnic and universities. The paper tried to ascertain if attitude of faculty to ICT correlates to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…The findings in Table 2 showed that gender had no significant influence in their attitude towards the usage of social media devices. This is in line with the finding in the research work done by Onwuagboke and Singh [20] who compared the attitude of the faculty member by gender and type of institute. The finding revealed no significant difference in attitude by gender towards the usage of Information, Communication and Technology (ICT) and in like manner, significant differences in attitude do not exist by type of institutions among the three types of tertiary institutions.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
See 3 more Smart Citations
“…The findings in Table 2 showed that gender had no significant influence in their attitude towards the usage of social media devices. This is in line with the finding in the research work done by Onwuagboke and Singh [20] who compared the attitude of the faculty member by gender and type of institute. The finding revealed no significant difference in attitude by gender towards the usage of Information, Communication and Technology (ICT) and in like manner, significant differences in attitude do not exist by type of institutions among the three types of tertiary institutions.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
“…As their understandings increase, achievement increases in all round activities. Alansari [20] noted the increase in achievement in "all ability levels (high, medium, low); higher-level thinking processes can result; a deeper level of understanding is possible and critical thinking is promoted." Again, in his research, he noted more positive peer interaction and understanding as they demonstrate social skills and render more social support for each other.…”
Section: Social Learning Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors indicated that this finding suggested that IT did not have any significant gender disparity. Similarly, a study conducted in Nigeria by Onwuagboke and Singh (2016) about the use of ICT in teaching and the attitude of male and female teachers in three tertiary institutions reported no significant differences in relation to gender.…”
Section: No Significant Difference Studiesmentioning
confidence: 92%